Effect of pH and Mexican Oregano (Lippia berlandieri Schauer) Essential Oil Added to Carboxymethyl Cellulose and Starch Edible Films on Listeria monocytogenes and Staphylococcus aureus - Addí Rhode Navarro-Cruz; Carlos Enrique Ochoa-Velasco; Francisco Javier Caballero-Alvarez; Martin Alvaro Lazcano-Hernández; Obdulia Vera-López; Aurelio López-Malo; Raul Avila-Sosa (Journal of Food Quality)
The aim of this work was to evaluate the effect of pH and Mexican oregano essential oil (MOEO) added to carboxymethyl cellulose (CMC) and starch (S) edible films on Listeria monocytogenes and Staphylococcus aureus. CMC and S edible films were formulated with different concentrations (0%, 0.25%, 0.50%, 0.75%, and 1%) of MOEO at different pH (5, 6, or 7). Antimicrobial assay was performed. Inhibition curves were fitted to the Fermi model. Significant differences (p<0.05) were found in tc (time to reduce 50% of microbial population) and a (slope of the curve around tc), being lower at acidic pH. For L. monocytogenes, CMC films exhibited a higher antimicrobial effectiveness (0.50% of MOEO) compared to S films which need a higher concentration of MOEO (0.75%). S. aureus was inhibited with CMC films at 0.50% MOEO and pH 5 and 6. Microbial modeling has allowed estimating key intrinsic factors as pH and MOEO concentration with the synergistic effect against two important food-borne pathogens.